The Effect of Sustainability Reporting on Cost of Capital and Corporate Reputation - Samsidar Samsidar (Dhana, 2026)
Sustainability reporting has become an essential component of modern corporate governance as organizations increasingly face demands for transparency regarding environmental, social, and governance (ESG) performance. Beyond fulfilling disclosure requirements, sustainability reporting is believed to influence corporate financial outcomes and reputational standing. This study aims to analyze the effect of sustainability reporting on cost of capital and corporate reputation. This research employs a quantitative approach using secondary data obtained from sustainability reports and financial statements of companies that implement sustainability disclosure practices. The sample consists of publicly listed companies selected through purposive sampling based on the availability of sustainability reporting and financial data. Data were analyzed using multiple regression analysis to examine the relationship between sustainability reporting, cost of capital, and corporate reputation. The results indicate that sustainability reporting has a significant negative effect on cost of capital, suggesting that comprehensive ESG disclosure reduces information asymmetry and investment risk, thereby lowering financing costs. In addition, sustainability reporting shows a positive and significant effect on corporate reputation, indicating that credible sustainability disclosures enhance stakeholder trust and strengthen corporate image in competitive markets. In conclusion, sustainability reporting functions as a strategic governance mechanism that improves financial efficiency while simultaneously strengthening corporate reputation through transparent and responsible disclosure practices.